2014
DOI: 10.1167/iovs.13-13120
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Reverse Thermal Gel Sustains the Release of Intravitreal Bevacizumab In Vivo

Abstract: PURPOSE. We assessed the in vivo release profile of bevacizumab from and biocompatibility of poly(ethylene glycol)-poly-(serinol hexamethylene urethane), or ESHU, a thermoresponsive hydrogel administered intravitreally for drug delivery.METHODS. The technical feasibility of injection was assessed quantitatively via mechanical testing. For in vivo studies, New Zealand White rabbit eyes were injected intravitreally with 0.05 mL of either: ESHU dissolved in 25 mg/mL bevacizumab, ESHU dissolved in PBS, or 25 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 26 publications
0
62
1
1
Order By: Relevance
“…The trend is consistent with other reports on intravitreal in situ gel injection. 22 The value of IOP elevation was not as high as other reports, because we injected 40 lL instead of 50 lL gel (as used by other authors) intentionally to minimize IOP elevation and allow faster recovery. Conditions associated with IOP elevation including cataract and retinal ganglion cell loss were not observed by BIO or histology.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The trend is consistent with other reports on intravitreal in situ gel injection. 22 The value of IOP elevation was not as high as other reports, because we injected 40 lL instead of 50 lL gel (as used by other authors) intentionally to minimize IOP elevation and allow faster recovery. Conditions associated with IOP elevation including cataract and retinal ganglion cell loss were not observed by BIO or histology.…”
Section: Discussionmentioning
confidence: 91%
“…However, although promising in vitro protein release has been demonstrated by this approach, 19,21 the in vivo performance was not satisfactory and has only been demonstrated in one study. 22 Moreover, hydrophobic interaction between protein and the polymer may potentially affect the chemical or physical stability of the protein. 24 The nontransparent appearance of these gels may also hinder its application in the eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic polymer hydrogel PEG is used in different biomedical application, has been tested for intravitreal administration of drugs [24,39] and is FDA approved for use intravitreally. The in vivo trials showed favorable biocompatibility but inadequate stability in vivo using PEG where the substance was largely tolerated with minor changes in retinal cytoarchitecture and GFAPupregulation, and minor electrophysiological changes [38].…”
Section: Our Previous Results and Our Hypothesismentioning
confidence: 99%
“…It would only require a simple implantation process into the vitreous cavity close to the limbus of the eye, and would not require suturing after implantation. Recently, there has been an emergence in several novel delivery systems, such as encapsulated cell technology (ECT) 24,25 , hydrogels 26 , and microfilms 27 . However, the method used in the current study for preparing and delivering the drug-resin complex is both easy to follow and inexpensive, thereby being more advantageous for use in a basic research environment.…”
Section: Introductionmentioning
confidence: 99%